2022
DOI: 10.3389/fmicb.2022.937683
|View full text |Cite
|
Sign up to set email alerts
|

Factors structuring microbial communities in highly impacted coastal marine sediments (Mar Menor lagoon, SE Spain)

Abstract: Coastal marine lagoons are environments highly vulnerable to anthropogenic pressures such as agriculture nutrient loading or runoff from metalliferous mining. Sediment microorganisms, which are key components in the biogeochemical cycles, can help attenuate these impacts by accumulating nutrients and pollutants. The Mar Menor, located in the southeast of Spain, is an example of a coastal lagoon strongly altered by anthropic pressures, but the microbial community inhabiting its sediments remains unknown. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 142 publications
1
5
0
Order By: Relevance
“…Furthermore, the Palauibacterales might have another restoring effect on the environment. In a recent study of Mar Menor (Spain) marine sediments, we observed a high relative abundance of PAUC43f in heavy-metal contaminated sediments ( 36 ). The most abundant PAUC43f OTU in these sediments shared 99.3% identity to the 16S rRNA gene sequence found in Carthagonibacter metallireducens (Sp.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…Furthermore, the Palauibacterales might have another restoring effect on the environment. In a recent study of Mar Menor (Spain) marine sediments, we observed a high relative abundance of PAUC43f in heavy-metal contaminated sediments ( 36 ). The most abundant PAUC43f OTU in these sediments shared 99.3% identity to the 16S rRNA gene sequence found in Carthagonibacter metallireducens (Sp.…”
Section: Resultsmentioning
confidence: 76%
“…A dataset was built with complete and partial 16S rRNA gene sequences, classified as “ PAUC43f marine benthic group ” retrieved from SILVA r138 database ( 34 ), marine invertebrates (corals and sponges from the Mediterranean Sea ( 35 )), and sediments from the Mar Menor lagoon (SE, Spain ( 36 )). For the following bioinformatic analyses, default settings were used unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of these negative impacts could also affect the sediment-associated microbiota, which is not only an important contributor to biogeochemical cycles but could also help to counteract these impacts by accumulating and managing nutrients and contaminants (Dash et al, 2013;Nzila, 2013;Rodrıǵuez et al, 2018). However, our knowledge of the microbial communities in the Mar Menor remains quite limited (Aldeguer-Riquelme et al, 2022).…”
Section: Introductionmentioning
confidence: 99%